Physiological Adaptations to Extreme Maternal and Allomaternal Care in Spiders - Junghanns, Anja; Holm, Christina; Schou, Mads Fristrup; Overgaard, Johannes; Malte, Hans; Uhl, Gabriele; Bilde, Trine (Frontiers in Ecology and Evolution, 2019)
Some semelparous species show terminal investment by suicidal offspring provisioning. This requires internal cellular disintegration for the production of regurgitated food and in preparation for the sacrifice of the female body to the offspring, however we have limited insights into the extent and costs of such physiological modifications. Extreme provisioning is hypothesized to be limited to reproducing individuals because it requires physiological alterations triggered by reproduction. However, non-reproducing helpers-at-the-nest have been shown to engage in suicidal provisioning, prompting us to ask whether helpers undergo similar physiological alterations to brood provisioning as mothers, which would represent an adaptation to cooperative breeding. Using an experimental approach, we investigated the physiological consequences of extended maternal care in the solitary spider Stegodyphus lineatus and the cooperative breeder S. dumicola, and whether non-reproducing helpers (virgin allomothers) in S. dumicola show physiological adaptations to brood provisioning. To identify costs of offspring provisioning, we determined the energy expenditure (standard metabolic rate; SMR) and tissue disintegration over the course of brood care. In both species, brood care is associated with elevated SMR, which was highest in allomothers. Brood care results in progressive disintegration of midgut tissue, which also occurred in allomothers. On experimental offspring removal, these responses are reversible but only until the onset of regurgitation feeding, marking a physiological ‘point-of-no-return’. The mechanism underlying the onset of physiological responses is unknown, but based on our finding of mature eggs in mothers and allomothers, as opposed to the undeveloped eggs in virgins of the solitary species, we propose that oocyte maturation is a central adaptation in non-reproducing helpers to provide terminal allomaternal care.